Perbandingan Metode Full Costing dengan Metode Activity Bassed Costing untuk Menentukan Harga Pokok Produksi di UD. Tiga Rasa Kraksaan Probolinggo - Khusnik Hudzafidah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
This study aims to analyze the comparison of full costing method with activity bassed costing method to determine Cost Of Goods Manufactured in UD Tiga Rasa Kraksaan (Iodized Salt Industry). This type of research is descriptive analysis, with variable Full Costing Method, Activity Based Costing Method, and Cost Of Goods Manufactured. The result of comparison research of Full Costing Method with Activity Based Costing Method on UD. Tiga Rasa Kraksaan (Iodized Salt Industry) during the period of 1-30 June 2015, Full Costing Method calculation to determine Cost Of Goods Manufactured Rp84.983.000. Whereas Activity Based Costing method get bigger result Rp 85.907.550, with difference to two method Rp 924.550. The difference that occurs, the Full Costing Method of production costs are charged only to one Costr Driver only, consequently tend to distort the loading of Factory Overhead Costs. In the Activity Based Costing Cost Factory Overhead Cost is charged to many Cost Drivers, so Activity Based Costing method is able to allocate the cost of activity to the product accurately and accurately based on the consumption of each activity.